Doris Salcedo: memórias da exclusão e violência - Costa, Maria Luiza Calim de Carvalho [UNESP] (My University, 2014)
The Colombian artist Doris Salcedo demonstrates, through his works, the universal vulnerability of human beings. The artist uses a concrete materiality such as furniture that is part of everyday life, and builds abstract works, sometimes unusual images, requiring the reader to excavate layers of memory and adjust his perception to decipher the poetic deviation and establish the sense. The theme is violence that humanity was and still been submitted in all corners of the world, particularly Latin America in the stories of oppression, dictatorships, civil wars, civil rights violated, etc. Her works echo the "silent scream" of the vulnerable.
Keywords: Latin America; Contemporary art; Doris Salcedo